HIV Prevention and Rehabilitation Models for Women Who Inject Drugs in Russia and Ukraine. (5th December 2012) - Yorick, Roman; Skipalska, Halyna; Suvorova, Svetlana; Sukovatova, Olga; Zakharov, Konstantin; Hodgdon, Sara
Abstract : Women who inject drugs require gender-specific approaches to drug rehabilitation, modification of risk behaviors, and psychosocial adaptation. Improved outcomes have been demonstrated when the specific needs of women's subpopulations have been addressed. Special services for women include prenatal care, child care, women-only programs, supplemental workshops on women-focused topics, mental health services, and comprehensive programs that include several of the above components. To address the special needs of women injecting drug user (IDU) subpopulations, such as HIV-positive pregnant women and women with young children, recently released female prisoners, and street-involved girls and young women, HealthRight International and its local partners in Russia and Ukraine have developed innovative service models. This paper presents each of these models and discusses their effectiveness and implementation challenges specific to local contexts in Russia and Ukraine.